International Cooperation in the Fight against Tax Evasion - Vybíral, Roman (Public Governance, Administration and Finances Law Review, 2019)
As regards the fight against tax evasion individual states do not act isolated, on the contrary the key role is being played by international organisations. Because of the wide fiscal sovereignty of states such cooperation takes many forms and outputs. On the one hand, this article aims to identify areas within which the fight against tax evasion occurs. Furthermore, it aims to analyse the development and current status of important international organisations that fight against tax evasion and to present their selected outputs.